1994
DOI: 10.1007/bf02102947
|View full text |Cite
|
Sign up to set email alerts
|

Understanding acute psychological distress following natural disaster

Abstract: A household probability sample of 229 adults was interviewed four to seven months afier the Sierra Madre earthquake (June 28, 1991; Los Angeles County). The study predicted psychological distress from these variables: demographics, traumatic event histoty, low magnitude event histoty, earthquake related threat perceptions, and earthquake related resource loss. Based on the Conservation of Resources (COR) stress model, it was predicted that resource loss would be central in predicting psychological distress. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
130
1
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 158 publications
(152 citation statements)
references
References 26 publications
19
130
1
2
Order By: Relevance
“…According to this principle it is the acute loss of resources, and not a stable, poor situation that would lead to all stress-outcomes. The primacy of resource loss principle has been proven among a variety of samples facing chronic stressors (e.g., Freedy et al, 1994;Holahan et al, 1999Holahan et al, , 2000Norris and Kaniasty, 1996). Recent evidence has, for instance, shown that the impact of chronic conditions of poverty on women's depression levels worked almost exclusively through secondary (material) loss (Ennis et al, 2000;Hobfoll et al, 2003).…”
Section: Applying Conservation Of Resources Theory and Ecological Anamentioning
confidence: 97%
See 1 more Smart Citation
“…According to this principle it is the acute loss of resources, and not a stable, poor situation that would lead to all stress-outcomes. The primacy of resource loss principle has been proven among a variety of samples facing chronic stressors (e.g., Freedy et al, 1994;Holahan et al, 1999Holahan et al, , 2000Norris and Kaniasty, 1996). Recent evidence has, for instance, shown that the impact of chronic conditions of poverty on women's depression levels worked almost exclusively through secondary (material) loss (Ennis et al, 2000;Hobfoll et al, 2003).…”
Section: Applying Conservation Of Resources Theory and Ecological Anamentioning
confidence: 97%
“…Disaster studies, too, have shown that resource loss resulting from fast-onset disasters appears to account for a significant amount of variance in psychological stress outcomes (Salzer and Bickman, 1999). Moreover, several studies have shown that resource loss was the most important factor in predicting stress outcomes, including post traumatic stress disorder, among victims of two types of disasters, namely earthquakes and hurricanes (Freedy et al, 1992(Freedy et al, , 1994Ironson et al, 1997).…”
Section: Applying Conservation Of Resources Theory and Ecological Anamentioning
confidence: 99%
“…Consistent with pathways models of mental health, PTSD is sensitive to a range of exposure and predisposing social and emotional factors, with young people particularly vulnerable (Salcioglu et al 2007). In addition to the development of severe anxiety disorders, traumatic exposures can also cause reactions ranging from general somatic and mental health problems, followed by resilient recovery to several types of enduring, severe psychopathology (Norris et al 2002), as well as loss of resources (Freedy et al 1994) and substantial psychological distress (Beaudoin 2007;Wickrama and Wickrama 2008).…”
Section: Direct Effects Of Climate Change On Mental Healthmentioning
confidence: 99%
“…reactions (Freedy, Saladin, Kilpatrick, Resnick, & Saunders, 1994), the psychological sequelae can persist for up to 3À5 years after a natural disaster (Lima et al, 1993). In the United States, over 8 million people suffer from posttraumatic stress disorder (PTSD) (National Institute of Mental Health, 2012).…”
Section: All Disastersmentioning
confidence: 99%